Predicting the sequence of mean propulsion forces during indoor wheelchair sports: a proof of concept - Chenier, F.; Aissaoui, R. (ISBS Proceedings Archive (Michigan), 2017)
Monitoring the push force is an important asset during wheelchair (WC) sports training. However, current instrumented wheels cannot be used without significantly altering the WC-user dynamics. Moreover, the push force could not be estimated directly from the WC acceleration because of the strong influence of the upper body movement on the WC-user dynamics. In this paper, we present a new method to predict the progression of the mean push force using temporal information (grab/release times) and kinematic information (WC velocity changes). This method was validated at two velocities with 17 manual WC users who propelled their own standard manual WC in an indoor hallway. When summed over both sides, the root-mean-square prediction error was 15.7 N at a comfortable velocity and 35.9 N at the maximum velocity. These results have great implications for indoor WC sports training.